ANALYSIS OF SECTIO CAESAREA UNIT COST AS A BASIS TO RECOMMEND THE PRICE - Widodo, Puguh Priyo; Hariyanto, Tatong; Djamhuri, Ali (Universitas Brawijaya, Indonesia, 2017)
This research aims to know the amount of Sectio Caesarea unit cost as a basis to recommend the price. Beside that this research also aims to know cost component which influences Sectio Caesarea unit cost and to know factoHospital that can influence counting Sectio Caesarea unit cost in the hospital. The method used in this research is Operational research and this research is descriptive with an approach to quantitative and qualitative data. Unit cost calculation using real cost method. The results show that Sectio Caesarea unit cost as a basis to recommend the price of Rp. 7,687,231.03. Hospital costs currently only reach CRR 102.86%. The proposed price of Section Caesarea amounted to Rp. 7,878,000.00. Cost components that affect the unit cost are direct costs, indirect costs, and utilization. FactoHospital affecting the calculation of the unit cost include never done a cost analysis, incomplete data, human resource capability, knowledge of human resources, and lack of skills of human resources. From these results Need to do a cost analysis, revamping financial statements, and equipment inventory.